Performance and physiological parameters of broiler chickens subjected to fasting on the neonatal period - Gonzales, E. [UNESP]; Kondo, N. [UNESP]; Saldanha, E. S. P. B.; Loddy, M. M. [UNESP]; Careghi, C.; Decuypere, E. (Elsevier, 2003)
Broiler chicks aged 12 h after hatching were allotted according to a block design in a 7 x 2 factorial schedule of 14 treatments and four replications of 50 chicks each one. The main experimental factors were fasting for 0, 6, 12, 18, 24, 30, and 36 h after chick placement and sex. Independent of sex, fasting had a negative linear effect on weight and productivity of broilers at market age (42 d) without affecting feed conversion or mortality index. Groups subjected to 18 and 36 h of fasting after placement, corresponding to 30 and 48 h posthatching fasting, had lower biometrical values for small intestine (length, weight, and size; villus height; and crypt depth) than chicks fed immediately after placement. According to the Pearson test, BW of birds at 21 and 42 d were significantly correlated to BW at 7 d (r = 0.77) and 21 d (r = 0.45), respectively. Males performed better than females but had higher mortality rates. Fasting did not influence serum concentrations of corticosterone or sexual steroid hormones. Nevertheless, early signs of sexual dimorphism arose from the high estradiol (E2) concentration on female serum. Heterophil:lymphocyte ratio was not different among treatments, indicating that early fasting did not seem to be a stress factor 21 or 42 d after fasting. The results suggested a maximum fasting of 24 h after hatching in order to preserve broiler productivity at market age.
Keywords: Chick; Fasting; Neonatal; Performance; Physiology; Aves; Gallus gallus; corticosterone; estradiol; sex hormone; aging; animal; blood; body weight; chicken; comparative study; diet restriction; female; growth, development and aging; histology; leukocyte count; male; newborn; organ size; physiology; sexual development; small intestine; yolk sac; Aging; Animals; Animals, Newborn; Body Weight; Chickens; Corticosterone; Estradiol; Female; Gonadal Steroid Hormones; Intestine, Small; Leukocyte Count; Male; Organ Size; Sex Characteristics; Yolk Sac